2016
DOI: 10.1007/s10704-015-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

A homogenization based yield criterion for a porous Tresca material with ellipsoidal voids

Abstract: International audienceThis paper presents a rate-independent ana- lytical model for porous Tresca ( J3 -dependent) mate- rials containing general ellipsoidal voids. The model is based on the nonlinear variational homogenization method which uses a linear comparison material to esti- mate the response of the nonlinear porous solid and is denoted as “MVAR”. Specifically, the model is derived by an original approach starting from a novel porous single crystal model (Mbiakop et al. in Int J Solids Struct 64–65:100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…E.7, it can be shown that g n π 3 = g n (0), g ′ n (0) = g ′ n π 3 = 0 and g n (θ) + g ′′ n (θ) ≥ 0, which will be useful in what follows. Note that in the limit in which n → +∞, the single crystal becomes a perfectly plastic Tresca material, as already pointed out by other studies (Cailletaud, 2009;Mbiakop et al, 2016), which means that: Appendix E.2. Hollow sphere under hydrostatic loading It is recalled that Benallal (2018) demonstrated that a hollow sphere with an isotropic perfect-plastic matrix following a yield function expressed as:…”
Section: Credit Authorship Contribution Statementmentioning
confidence: 67%
“…E.7, it can be shown that g n π 3 = g n (0), g ′ n (0) = g ′ n π 3 = 0 and g n (θ) + g ′′ n (θ) ≥ 0, which will be useful in what follows. Note that in the limit in which n → +∞, the single crystal becomes a perfectly plastic Tresca material, as already pointed out by other studies (Cailletaud, 2009;Mbiakop et al, 2016), which means that: Appendix E.2. Hollow sphere under hydrostatic loading It is recalled that Benallal (2018) demonstrated that a hollow sphere with an isotropic perfect-plastic matrix following a yield function expressed as:…”
Section: Credit Authorship Contribution Statementmentioning
confidence: 67%
“…There has been significant research performed in this area in the recent past; these works have been thoroughly reviewed and discussed in the literature, for example by incorporating crystallographic aspect for anisotropic behaviour (Besson, 2010; Mbiakop et al., 2016; Han et al., 2013; Mbiakop et al., 2015; Paux et al., 2015; Song and Castañeda, 2017 and references therein) or anisotropy through phenomenological plasticity models (for details see Benzerga and Leblond, 2010; Benzerga et al., 2016; Besson, 2010). These works are based on Gurson-type approach (for details see Benzerga and Leblond, 2010; Benzerga et al., 2016; Besson, 2010; Paux et al., 2015 and references therein) and homogenisation approaches (Mbiakop et al., 2016; Han et al., 2013; Mbiakop et al., 2015; Song and Castañeda, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These types of micro-mechanical estimates have been applied to various combinations of morphologies and local strength properties for instance by [15,29,22,13,1,31,2,49,14,53]. Most of these estimates do not however model third invariant effects at the macroscopic scale, except works by [44,3], who revisited the limit analysis problem on the Gurson hollow sphere, and by [10,32,33] using a "second-order" non-linear homogenization method.…”
Section: Introductionmentioning
confidence: 99%
“…Simple 3D representations of the porous medium have then been considered, such as pores in simple cubic, body centered cubic or face centered cubic periodic configurations [45,34] as well as the hollow sphere [41]. More representative microstructures involving multiple pores have only recently been considered [58,4,5,17,18,57,53,32,33], but are limited to approximately 50 pores. Most of the simulations where discretized using the Finite Elements Method (FEM) and solved either by solving an incremental elasto-plastic problem or directly by resorting to second-order programming solvers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation